Effects of Polygonum multiflorum Root Extract in Methanol on Pigment Formation of Zebrafish Embryo - Diep, Pham Ngo; Thanh, Nguyen Lai; Thang, Nguyen Dinh (VNU Journal of Science: Natural Sciences and Technology, 2016)
Abstract: In this study, we investigated the effects of Polygonum multiflorum (PM) root extract in methanol on developments of teratogenic defects as well as the changing of transcript levels of molecules related to melanin formation in embryos of wild type strain AB zebrafish. Our results showed that PM root extract contributed an important role in melanin formation in zebrafish embryos via activation of MC1R/MITF/tyrosinase pathway. However we also found that, at the high concentration (above 225 mg/L), PM root extract acted as an agent for developments of teratogenic defects, including: heart/yolk-sac oedema, haemovascular defect with appearing of red dots accumulation; yolk/head/body necrosis; abnormal trunk with curved tail/body in zebrafish embryos. Taken together, we suggest that despite Polygonum multiflorum has been traditionally  used as a traditional drug or an ingredient of drugs or cosmetics for early gray hair treatment and/or other diseases for a long time, it should be further carefully investigated the biological effects of PM root extract before using as a drug in clinic, especially for pregnant women.  Keywords: Polygonum multiflorum , graying hair, melanin, MITF, Tyrosinase, zebrafish.